2018
DOI: 10.1177/0954406218771997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size and volume fraction on the strengthening mechanisms of boron carbide reinforced aluminum metal matrix composites

Abstract: In the present work, 6061 Al–B4C metal matrix composites with different volume fractions (5, 10, 15 and 20 vol.%) have been fabricated by a low cost modified stir casting technique. The effect of varying particulate content on the microstructure of Al–B4C composites has been qualitatively characterized using a scanning electron microscope and an optical microscope. Tensile tests were performed to study the influence of varying reinforcement content on the strengthening behavior of fabricated composites. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…70 According to equation (6), f ′ d-EM was the second-highest improvement factor contributing to the increase in yield strength of both N-AMCs and M-AMCs (Figure 13). This result is consistent with the study of Sekine and Chen 44 investigating the yield strength of SiC particle-reinforced Al-based composites produced by the stir casting method; on the other hand, the opposite result was obtained in the study of Raj and Thakur 46 investigating the strengthening mechanisms in Al-based composites reinforced with B 4 C particles. It can be attributed to the differences in the values of some variables, such as the type of reinforcement particles and process temperatures.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…70 According to equation (6), f ′ d-EM was the second-highest improvement factor contributing to the increase in yield strength of both N-AMCs and M-AMCs (Figure 13). This result is consistent with the study of Sekine and Chen 44 investigating the yield strength of SiC particle-reinforced Al-based composites produced by the stir casting method; on the other hand, the opposite result was obtained in the study of Raj and Thakur 46 investigating the strengthening mechanisms in Al-based composites reinforced with B 4 C particles. It can be attributed to the differences in the values of some variables, such as the type of reinforcement particles and process temperatures.…”
Section: Resultssupporting
confidence: 91%
“…Various analytical equations and models have been developed and modified to predict the effects of the size, volume fraction, and type of the reinforcement particles on the strengthening mechanisms in the PRMMCs. 3845 However, these models neglect the influence of at least one or more strengthening mechanisms and predict overestimated results compared to experimental results 46 since it is assumed that the reinforcement particles are uniformly distributed in the matrix and that the bond between the reinforcement particles and the matrix is strong. Moreover, none of these models take into account the negative influence of porosity in predicting the strength of the PRMMCs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the used fly-ash is rich in SiO 2 and Al 2 O 3 content i.e., 61.04 and 24.96%, respectively, and which are responsible for enhancing the properties of the composite. Magnesium (Mg) powder and potassium-hexa-flurotitanate (K 2 TiF 6 ) flux have been added into the melt during the stirring process as wetting agents to improve the wettability of fly-ash and boron carbide with aluminum [58,64,65]. Table 5 shows the list of optimal stir casting parameters that are being used for the fabrication of hybrid composites to achieve a homogeneous distribution of reinforcements and to avoid the accumulation of reinforcements into the matrix phase.…”
Section: Experimental Details Composite Preparationmentioning
confidence: 99%
“…The steps involved in the stir casting process are preheating, melting, stirring, pouring, and solidification. Initially, the aluminum 7075 was preheated at 850 • C, while simultaneously the mixture of boron carbide and flyash were also preheated at 300 • C for 2 h [58,64,65,68]. The mechanical stirrer of the impeller blade angle is 30 • , the impeller blade diameter is 50% of the crucible diameter, and this is introduced in the melt and stirred at 550 rpm.…”
Section: Experimental Details Composite Preparationmentioning
confidence: 99%
“…%) via a low-cost modified stir-casting technique and strengthening mechanisms were quantitatively analyzed as a function of particle size and volume fraction. 16 Al-Mosawi et al prepared an Al-based composite containing 2, 4, 7, and 10 vol. % volume fractions of α-Al 2 O 3 via hot pressing, and microstructure–mechanical property correlations were obtained as functions of α-Al 2 O 3 volume fraction.…”
Section: Introductionmentioning
confidence: 99%